NEUROPSYCHOLOGY OF PERCEPTION AND FACIAL EXPRESSION OF EMOTIONS: STUDIES WITH CHILDREN AND NON HUMAN PRIMATES - Loeches Alonso, Angela; Carvajal Molina, Fernando; Serrano, J. M.; Fernández Carriba, Samuel (Anales de Psicología / Annals of Psychology, 2004)
This study reviews different researches on the neuropsychology of facial perception and expression of emotions in children and non-human primates. It parts from neodarwinian theories on the origin of the emotion that take into account the existence of specific cerebral circuits for the expression and understanding of affect, and consider such behaviours as innate and phylogenetically determined. From literature reviewed, the main conclusions that can be extracted are the following ones: (1) During the first year of life infants show basic abilities to recognize emotions. Among other neurobiological correlates, it has been observed that this process corresponds with a greater activity of the right hemisphere, as opposed to the left one. (2) From different experimental approaches, human and non-human primates show a similar pattern in the recognition and discrimination of facial expressions of emotions. (3) Infants express emotions with similar muscular actions to those described in adults. Most of the authors also point out a greater involvement of the right hemisphere than the left one, for all of the emotional expressions. However, some studies report that right hemisphere is dominant only for the negative expressions, while the left hemisphere is for the positive ones. (4) Studies on facial expression in human and non-human primates show an asymmetry in the production of emotional responses with a greater involvement of the left side of the face (right cerebral hemisphere). This review concludes that the existence of anatomical and functional similarities in non-human primates, children and adults justifies the interest by the ontogenetic and phylogenetic studies in order to understand the neurobiological bases underlying emotional behaviour.